Study the Characterizations of Cement Mortar by Nano Pozzolanic Materials Additions - Fadhil A. Rasin (Al-Khawarizmi Engineering Journal, 2018)
This study involves adding nano materials and interaction with cement mortar behavior for several mortar samples under variable curing time with constant water to cement ratio (W/C = 0.5). The effects of adding nano materials on the microstructure of cement mortar were studied by (Scanning Electronic Microscopy (SEM) and X-Ray (for samples at different curing time 28 and 91 days. Small ratio replacements of nano particles (SiO2 or Al2O3) were added to Ordinary Portland Cement (OPC) type (I). The percentage of nano materials additives replacement by weight of ordinary Portland cement includes (1, 2, 3, 4 and 5%) for both types of nano materials with constant (W/C) ratio, also the amount of the fine aggregate used was three times the amount of cement. The results showed that, the mortar consist of both nano materials had better microstructure than mortar without nano materials in all test. Best enhancements in properties and microstructure for mortars with nano silica were achieved with (3%) additives while were achieved with nano alumina at (2%) additives.